New findings in the roles of Cyclin-dependent Kinase inhibitors 2B Antisense RNA 1 (CDKN2B-AS1) rs1333049 G/C and rs4977574 A/G variants on the risk to coronary heart disease. Issue 1 (1st January 2020) - Yuan, Wei; Zhang, Wei; Zhang, Wei; Ruan, Zhong-Bao; Zhu, Li; Liu, Yu; Mi, Yuan-Yuan; Zhang, Li-Feng
ABSTRACT: The relationship between Cyclin-Dependent Kinase Inhibitors 2B Antisense RNA 1 ( CDKN2B-AS1 ) variants rs1333049 G/C and rs4977574 A/G and the risk of coronary heart disease is unclear. We conducted an update analysis incorporating odds ratios and 95% confidence intervals to assess the correlation. Furthermore, we used in silico analysis to investigate the genes and proteins that interact with CDKN2B. Fifty case-control studies with a sample size of 35, 915 cases and 48, 873 controls were involved. We revealed that the rs1333049 C allele could increase the risk of coronary heart disease in the overall analysis (allele comparison, OR = 1.13, 95%CI = 1.05–1.21, P = 0.001; homozygous contrast, OR = 1.29, 95%CI = 1.11–1.49, P = 0.001; dominant comparison, OR = 1.14, 95%CI = 1.03–1.27, P = 0.011; recessive comparison, OR = 1.21, 95%CI = 1.10–1.34, P < 0.001). In subgroup analysis, positive correlations were detected in studies involving West and East Asians and in population-based control studies. The rs4977574 G allele was also a risk factor for coronary heart disease (allelic comparison, P = 0.001; heterozygous comparison, P = 0.003; homozygous comparison, P < 0.001; dominant comparison, P = 0.001). These results indicate correlation of CDKN2B-AS1 rs1333049 G/C and rs4977574 A/G variants may be correlated with the risk of coronary heart disease. Abbreviations CDK: Cyclin Dependent Kinase; CCND: G1/S-specific cyclin-D; CDKN: Cyclin Dependent Kinase Inhibitor; GWAS: Genome-wide association study; CDKN2B-AS1: Cyclin-Dependent Kinase Inhibitors 2B Antisense RNA 1; CHD: Coronary heart disease; MAF: minor allele frequencies; HWE: Hardy-Weinberg equilibrium of controls; CI: confidence interval; COL8A2: Collagen type VIII alpha 2 chain; HB: Hospital-based; ORs: odds ratios; ITGA11: Integrin subunit alpha 11; LTBP: Latent transforming factor beta binding protein; PB: Population-based; IBC: Itmat Broad Care; NA: Not applicable; PCR-RFLP: polymerase chain reaction-restriction fragment length polymorphism; MI: Myocardial Infarction; SNP: single nucleotide polymorphism; SMAD: Mothers against decapentaplegic homolog; RT-PCR: Real-time polymerase chain reaction; UK: United Kingdom Graphical abstract: